Empowering Adult Learners of Slums Communities: TeleSchool as a Pathway for Literacy Skills Development - Noor Ahmed Khan (IJLTP, 2025)
This study was done on the “Empowering Adult Learners of Slums Communities: TeleSchool as a Pathway for Literacy Skills Development”. TeleSchool program to develop literacy skills among adult learners; b) to evaluate the effectiveness of TeleSchool program for adult learners regarding improvement in their knowledge. Sample consisted of 10 adult learners enrolled in selected Adult Literacy Centre for session 2021-22 taken by using systematic random sampling technique. List of enrolled adult learners of the target Adult Literacy Center was arranged alphabetically, and Kth value was applied to determine the participant of for research study. Sample size (34.5%) was selected from the selected Adult Literacy Centre (ALC). A test on TeleSchool programs broadcasted and recorded videos of contents/learning were used to check the literacy skills development among adult learners. This scale was content validated by seeking expert opinion. Tele-school recorded videos programs on literacy skills were shown to the sample’s participants for one month. Before showing the videos, a pre-test was taken from the participants and then post-test was administered after treatment. Data was analyzed by applying descriptive and inferential statistics. Major results inferred that there was significant difference between pre and post test results which indicated that TeleSchool program is very effective for enhancement of adult learners’ literacy skills (more in reading and understanding ability of Urdu language, less in English readings and understanding, enhancement in their Islamic knowledge, enhancement in their basic mathematic / counting skills). Majority of adult learners of slums communities (88%) agreed that TeleSchool program played very vital role for enhancement in their general knowledge which spectacles effectiveness of the program for adult learners. Based on the study findings, it is concluded that majority of adult learners’ slums communities agreed that TeleSchool program played positive role for enhancement in literacy skills’ acquisition.